Facility-based maternal death reviews: effects on maternal mortality in a district hospital in Senegal - Dumont Alexandre; Gaye Alioune; Bernis Luc de; Chaillet Nils; Landry Anne; Delage Joanne; Bouvier-Colle (The World Health Organization, 2006)
OBJECTIVE: The improvement of obstetric services is one of the key components of the Safe Motherhood Programme. Reviewing maternal deaths and complications is one method that may make pregnancy safer, but there is no evidence about the effectiveness of this strategy. The objective of our before and after study is to assess the effect of facility-based maternal deaths reviews (MDR) on maternal mortality rates in a district hospital in Senegal that provides primary and referral maternity services. METHODS: We included all women who were admitted to the maternity unit for childbirth, or within 24 hours of delivery. We recorded maternal mortality during a 1-year baseline period from January to December 1997, and during a 3-year period from January 1998 to December 2000 after MDR had been implemented. Effects of MDR on organization of care were qualitatively evaluated. FINDINGS: The MDR strategy led to changes in organizational structure that improved life-saving interventions with a relatively large financial contribution from the community. Overall mortality significantly decreased from 0.83 (95% CI (confidence interval) = 0.60 -1.06) in baseline period to 0.41 (95% CI = 0.25 -0.56) per 100 women 3 years later. CONCLUSION: MDR had a marked effect on resources, management and maternal outcomes in this facility. However, given the design of our study and the local specific context, further research is needed to confirm the feasibility of MDR in other settings and to confirm the benefits of this approach for maternal health in developing countries.